Distributed Coordination Control of First- and Second-Order Multiagent Systems with External Disturbances. (11th November 2015) - Mo, Lipo; Pan, Tingting; Guo, Shaoyan; Niu, Yuguang
Abstract : This paper is devoted to the coordination control problem of heterogeneous first- and second-order multiagent systems with external disturbances. First, by applying the theory of eigenvalue and the method of model transformation, the consensus state of heterogeneous multiagent systems is obtained. Then, based on the consensus state, the control output is defined, and sufficient conditions are derived to make all agents reach consensus withH ∞ performance. Finally, simulation results are provided to demonstrate the effectiveness of the presented results.